Climate change and invasion by intracontinental range-expanding exotic plants: the role of biotic interactions - Morriën, Elly (Oxford University Press, 2010)
BACKGROUND AND AIMS: In this Botanical Briefing we describe how the interactions between plants and their biotic environment can change during range-expansion within a continent and how this may influence plant invasiveness. SCOPE: We address how mechanisms explaining intercontinental plant invasions by exotics (such as release from enemies) may also apply to climate-warming-induced range-expanding exotics within the same continent. We focus on above-ground and below-ground interactions of plants, enemies and symbionts, on plant defences, and on nutrient cycling. CONCLUSIONS: Range-expansion by plants may result in above-ground and below-ground enemy release. This enemy release can be due to the higher dispersal capacity of plants than of natural enemies. Moreover, lower-latitudinal plants can have higher defence levels than plants from temperate regions, making them better defended against herbivory. In a world that contains fewer enemies, exotic plants will experience less selection pressure to maintain high levels of defensive secondary metabolites. Range-expanders potentially affect ecosystem processes, such as nutrient cycling. These features are quite comparable with what is known of intercontinental invasive exotic plants. However, intracontinental range-expanding plants will have ongoing gene-flow between the newly established populations and the populations in the native range. This is a major difference from intercontinental invasive exotic plants, which become more severely disconnected from their source populations.